The impact of exurban development on forested areas in Kurgan City, Russia. (May 2020) - Ponstingel, Daria
Highlights: Forest and grassland around Kurgan City have decreased from 1990 to 2011, with forested areas decreased by 40.75 percent. Developed land (including infrastructure) and agricultural land increased by 5.46 percent and 1023.20 percent respectively. The mean NDVI values decreased by 3.4 percent, the mean NDVI values for the forested areas decreased by 41.15 percent. There are ten planned exurban communities to be built, which will increase the amount of developed land by ∼37.4 percent. This paper proposes a green belt policy in Kurgan City as a way to protect forested areas from residential development. Abstract: Exurban communities—a significant form of urban sprawl—can transform natural land cover. Exurban development refers to an expansion of communities located outside a city and its suburbs. One of the main reasons these settlements develop is a desire by residents to live closer to nature and developers' recognition of the profitability of addressing this desire. Additionally, exurbs can become prosperous regions settled by people with high income. However, exurban development not only directly affects community patterns, but also species patterns, habitat reduction and disconnection, as well as land cover and land use alterations. The purpose of this paper is a quantitative analysis of the land cover transformation and forest fragmentation in Post-Soviet Russia, based on an empirical case study of the city of Kurgan. This case study also contributes to the overall research of urban sprawl in Russian provinces by adding to the discussion of homeowners' behavior, regional environmental policies, and their role concerning the impacts of exurban settlements on the natural environment. This paper uses remote sensing imagery, census data, and primary data to analyze land cover change due to the emergence of exurban communities around Kurgan, Russia, with specific emphasis on the changes to native vegetation resulting from human behavior and stakeholder preferences.